Oh **UK! Whatever Next? Multimodal Humour on Brexit-Related Covers of The Economist - Miller Dorota (Studia Anglica Posnaniensia)
Brexit has undoubtedly been one of the most hotly debated topics in both European and world politics, setting a precedent in the history of European integration. Despite its unquestionably serious repercussions, a considerable part of Brexit media coverage was aimed at amusing the audience. An example of this includes Brexit-related covers of The Economist.